Determining the accuracy of gestation feed drops - Schneider, J.D.; Tokach, Michael D.; Goodband, Robert D.; Nelssen, Jim L.; DeRouchey, Joel M.; Dritz, Steven S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2009)
An experiment was conducted to determine the accuracy of three different gestation feed drops. Each drop was tested at three different angles (90, 75, 60°) from the feed line. Feed was collected and weighed at feeder settings of 2, 4, 6, 8, and 10 lb for the Econo- Drop and Accu-Drop feed dispensers. Samples were taken at 2, 4, 6, and 8 lb for the Ultra- Drop feed dispenser due to a smaller storage capacity for feed with this feed drop. There were five replications (five drops of each type) at each feed setting. There was a drop type by angle interaction (P<0.01) for the feed dispenser settings versus the actual pounds of feed dropped. At angles of 90 or 60 degrees, the Accu-Drop and the Ultra-Drop feed dispensers more (P<0.10) accurately dropped the correct amount of feed at the respective feeder settings. The amount of feed dropped at each dispenser setting was influenced more by angle to the feed line with the Econo-Drop than with the Accu-Drop or Ultra- Drop feed dispensers. This study demonstrated that the Accu-Drop and the Ultra-Drop feed dispensers are more accurate than the Econo-Drop feed dispenser. Therefore, producers should consider the additional feed cost over the lifetime of the feed drops and not rely solely on initial price.
Keywords: Swine; Feed drops; Feed cost; Slope-intercept